RETRACTED: Altitude Cardiomyopathy Is Associated With Impaired Stress Electrocardiogram and Increased Circulating Inflammation Makers - Shi, Ya-Jun; Wang, Jin-Li; Gao, Ling; Wen, Dong-Lin; Dan, Qing; Dong, Ying; Guo, Ya-Tao; Zhao, Cheng-Hui; Li, Teng-Jing; Guo, Jun; Li, Zong-Bin; Chen, Yun-Dai (Frontiers in Physiology, 2021)
Many sea-level residents suffer from acute mountain sickness (AMS) when first visiting altitudes above 4000 m. Eighty young men from a military academy underwent a standard treadmill exercise test (TET) and biochemical blood test at sea level, SHHC, and 4000-m altitude, sequentially, between December 2015 and March 2016. Exercise-related variables and 12-lead electrocardiogram parameters were obtained. Exercise intensity and AMS development were investigated. After exposure to high altitude, the count of white blood cells, alkaline phosphatase and serum albumin were increased (P<0.05). There were no significant differences in exercise time and metabolic equivalents (METs) between SHHC and high-altitude exposures (7.05 ± 1.02 min vs. 7.22 ± 0.96 min, P = 0.235; 9.62 ± 1.11 vs. 9.38 ± 1.12, P = 0.126, respectively). However, these variables were relatively higher at sea level (8.03 ± 0.24. min, P < 0.01; 10.05 ± 0.31, P < 0.01, respectively). Thus, subjects displayed an equivalent exercise tolerance upon acute exposure to high altitude and to SHHC. The trends of cardiovascular hemodynamics during exercise under the three different conditions were similar. However, both systolic blood pressure and the rate‒pressure product at every TET stage were higher at high altitude and under the SHHC than at sea level. After acute exposure to high altitude, 19 (23.8%) subjects developed AMS. Multivariate logistic regression analysis showed that METs under the SHHC (odds ratio [OR] 0.355 per unit increment [95% confidence intervals (CI) 0.159‒0.793]), P = 0.011), diastolic blood pressure (DBP) at rest under SHHC (OR 0.893 per mmHg [95%CI 0.805‒0.991], P = 0.030), and recovery DBP 3 minutes after exercise at sea level (OR 1.179 per mmHg [95%CI 1.043‒1.333]), P = 0.008) were independently associated with AMS. The predictive model had an area under the receiver operating characteristic curve of 0.886 (95%CI 0.803‒0.969, P < 0.001). Thus, young men have similar exercise tolerance in acute exposure to high altitude and to SHHC. Moreover, AMS can be predicted with superior accuracy using characteristics easily obtainable with TET.